Performance Evaluation and Benchmarking: 13th TPC Technology Conference, TPCTC 2021, Copenhagen, Denmark, August 20, 2021, Revised Selected Papers - Nambiar, Raghunath; Poess, Meikel (Lecture Notes in Computer Science, 2022)
This book constitutes the refereed post-conference proceedings of the 13th TPC Technology Conference on Performance Evaluation and Benchmarking, TPCTC 2021, held in August 2021.The 9 papers presented were carefully reviewed and selected from numerous submissions. The TPC encourages researchers and industry experts to present and debate novel ideas and methodologies in performance evaluation, measurement, and characterization.